Efficacy and safety of intraperitoneal ropivacaine in pain management following laparoscopic digestive surgery: A systematic review and meta-analysis of RCTs - Daghmouri, Mohamed Aziz; Chaouch, Mohamed Ali; Deniau, Benjamin; Benayoun, Laurent; Krimi, Bassem; Gouader, Amine; Oweira, Hani (Medicine, 2024)
Background: - Managing postoperative pain effectively with an opioid-free regimen following laparoscopic surgery (LS) remains a significant challenge. Intraperitoneal instillation of ropivacaine has been explored for its potential to reduce acute postoperative pain, but its efficacy and safety are still under debate. This study aimed to evaluate the efficacy and safety of intraperitoneal instillation of ropivacaine for acute pain management following laparoscopic digestive surgery. - Methods: - We used PRISMA 2020 and a measurement tool to assess systematic reviews 2 guidelines to conduct this review. The random-effects model was adopted using Review Manager Version 5.4 for pooled estimates. - Results: - We retained 24 eligible RCTs involving 1705 patients (862 patients in the intraperitoneal instillation group and 843 patients in the control group). The intraperitoneal instillation group reduced total opioid consumption during the first 24 hours postoperatively (MD = −21.93 95% CI [−27.64, −16.23], P < .01), decreased pain scores at different time (4 hours, 8 hours, 12 hours and 24 hours), shorter the hospital stay (MD = −0.20 95% CI [−0.36, −0.05], P < .01), reduced the postoperative shoulder pain (MD = 0.18 95% CI [0.07, 0.44], P < .01), and decreased postoperative nausea and vomiting (MD = 0.47 95% CI [0.29, 0.77], P < .01). - Conclusion: - Intraperitoneal instillation of ropivacaine appears to be an effective component of multimodal pain management strategies following laparoscopic digestive surgery, significantly reducing opioid consumption and improving postoperative recovery markers. Despite these promising results, additional high-quality trials are needed to confirm the efficacy and safety of this approach. - Registration: - The registration number at PROSPERO was CRD42021279238.
Gesehen am 17.02.2025